In-Hospital acute ischemic stroke following ST-elevation myocardial infarction - Albaeni, Aiham (Int J Cardiol Heart Vasc, 2020)
BACKGROUND: In-hospital ischemic stroke following acute ST-elevation myocardial infarction (STEMI) has not been evaluated on a national scale in the United States. METHODS: We used 2003 to 2014 Nationwide Inpatient Sample data to identify adults with a principal diagnosis of STEMI. Patients were divided into two groups defined by presence or absence of ischemic stroke. Clinical characteristics and in-hospital outcomes were studied using relevant statistics. Multiple linear and logistic regression models identified factors associated with ischemic stroke, national trend of in-hospital stroke incidence and in-hospital mortality. RESULTS: Of 1,842,529 STEMI patients hospitalized from 2003 to 2014, 22,268 (1.2%) developed acute in-hospital ischemic stroke. Those with acute strokes were older (age ≥ 65 years: 70% vs 46%), more likely female (51% vs 33%), and had higher rates of atrial fibrillation (28.9% vs 12.2%) and heart failure (40.5% vs 21.1%). Age and gender adjusted incidence of in-hospital ischemic stroke following STEMI remained stable; 1.4% in 2003 and 1.5% in 2014 (P trend = 0.50). However, age and gender adjusted in-hospital mortality declined in STEMI patients with and without in-hospital ischemic stroke [AOR 0.97 (0.95–0.99) P trend = 0.03, and AOR 0.98 (0.98–0.99) P trend < 0.001, respectively]. Patients with ischemic strokes had higher in-hospital mortality (25.7% Vs 7.2%, p < 0.001), [AOR 2.11, 95% CI (1.92–2.32)]. CONCLUSION: In the United States, the incidence of acute in-hospital stroke remained stable from 2003 to 2014 following STEMI with significant decrease of in-hospital mortality trends. Despite slight improvement in mortality trends, in-hospital mortality rates remained elevated calling for interventions to optimize health care delivery.